Preventive Activities of the National Police of Ukraine to Counteract Domestic Violence under the Current Scenario - Dzhafarova, Olena; Ishchenko, Ivan; Kirika, Diana; Kachynska, Maryana; Riazantseva, Iryna (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2023)
The purpose of the research is to examine the preventive activities of the National Police of Ukraine to counteract domestic violence under the current scenario. The article analyzes the main regulatory legal acts of Ukraine that regulate the adoption of urgent measures to prevent and counteract domestic violence and gender-based violence and protect the rights of persons affected by such violence. The main tasks and methods of the preventive units of the National Police of Ukraine include identification of facts of domestic violence and timely response to them; receiving and reviewing applications and reports of domestic violence, including consideration of reports received by the call center for preventing and countering domestic violence, gender-based violence, violence against children, etc. The methodological basis of the research is presented as comparative-legal and systematic analysis, the formal-legal method, the interpretation method, the hermeneutic method, as well as methods of analysis and synthesis. It is determined that the legislation of Ukraine in the field of countering and preventing domestic violence includes legislative and bylaws, departmental, and regulatory legal acts. It is noted that units of the National Police of Ukraine exercise powers in the field of preventing and countering domestic violence, taking into account international standards for the response of law enforcement agencies to cases of domestic violence and risk assessment. The general and special measures applied to abusers are specified, as well as the specifics of their application by the preventive units of the National Police of Ukraine in the field of preventing and countering domestic violence.